Respuesta :
Answer:
[tex]y_\circ= 28.911[/tex]
Step-by-step explanation:
Given,
[tex]y'+\frac{2}{3}y=1-\frac{1}{2} t[/tex]
Integrating factor=[tex]e^{\int{\frac{2}{3} dt}}=e^{\frac{2}{3}t}[/tex]
Multiplying the integrating factor
[tex]e^{\frac{2}{3}t} y'+\frac{2}{3}e^{\frac{2}{3}t}}y=e^{\frac{2}{3}t}}-\frac{1}{2} e^{\frac{2}{3}t}}t[/tex]
Integrating both sides
[tex]\int (e^{\frac{2}{3}t} y'+\frac{2}{3}e^{\frac{2}{3}t}}y)dt=\int (e^{\frac{2}{3}t}}-\frac{1}{2} e^{\frac{2}{3}t}}t)dt[/tex] Let [tex]I=\int e^{\frac{2}{3}t}t dt[/tex]
[tex]\Rightarrow e^{\frac{2}{3}t}}y=\frac{21}{8}e^{\frac{2}{3}t}}-\frac{3}{4} e^{\frac{2}{3}t}}t+C[/tex] [tex]=t\int e^{\frac{2}{3}t}dt - \int[\int e^{\frac{2}{3}t}dt\times \frac{d}{dt} (t)]dt[/tex]
[tex]=\frac{3te^{\frac{2}{3}t} }{2} -\frac{9}{4} e^{\frac{2}{3}t} }[/tex]
Given,y(0)=y₀
[tex]\Rightarrow e^{\frac{2}{3}t}}y_\circ=\frac{21}{8}e^{\frac{2}{3}\times 0}}-\frac{3}{4} e^{\frac{2}{3} \times 0}}\times 0+C[/tex]
[tex]\Rightarrow C=e^{\frac{2}{3}t}}y_\circ-\frac{21}{8}[/tex]
[tex]\therefore e^{\frac{2}{3}t}}y=\frac{21}{8}e^{\frac{2}{3}t}}-\frac{3}{4} e^{\frac{2}{3}t}}t+e^{\frac{2}{3}t}}y_\circ-\frac{21}{8}[/tex]
y(t)=0
[tex]\therefore 0 =\frac{21}{8}e^{\frac{2}{3}t}}-\frac{3}{4} e^{\frac{2}{3}t}}t+e^{\frac{2}{3}t}}y_\circ-\frac{21}{8}[/tex]
[tex](y_\circ-\frac{21}{8} )e^{\frac{-2}{3} t}=\frac{3}{4}t -\frac{21}{8}[/tex]
Again since this solution has slope zero when it is just touche the t-axis.
y'(t)=0
[tex](y_\circ-\frac{21}{8} )e^{\frac{-2}{3} t}=\frac{9}{8}[/tex]
[tex]\Rightarrow \frac{3}{4}t -\frac{21}{8}=\frac{9}{8}[/tex] [tex][(y_\circ-\frac{21}{8} )e^{\frac{-2}{3} t}=\frac{3}{4}t -\frac{21}{8}][/tex]
[tex]\Rightarrow t=5[/tex]
Therefore
[tex](y_\circ-\frac{21}{8} )e^{\frac{-2}{3} 5}=\frac{3}{4}\times5 -\frac{21}{8}[/tex]
[tex]\Rightarrow y_\circ= 28.911[/tex]